WOMEN POWER TO END THE OPPRESSIONS OF PATRIARCHY IN SUSAN GLASPELL’S PLAY ‘TRIFLES’ - Asianti, Dwi Anggara (Language Circle: Journal of Language and Literature, 2012)
In patriarchy society, women do not have other choice but obey all rules set by men. As a result, women’s life marginalized and gap between women’s role and men’s occurred.The same condition and situation faced by a woman, as the main character, in Susan Glaspell’s entitled ‘Trifles’. This paper would like to identify the patriarchy oppressions and analyze action as the reflection of women’s power to end the oppressions of patriarchy. The women power, subtle and indirect, that may the women themselves never realize they have it